Implementation of Discovery Learning on Student Activeness and Learning Outcomes in Automotive Electricity Learning at Vocational High Schools - Dwi Jatmoko; Agung Setiawan; Amirudin Amirudin; Edi Tetra Wibowo; Muhamad Nurkholis (LITERACY : International Scientific Journals of Social, Education, Humanities, 2024)
This study was motivated by the low activeness and learning outcomes of students in the subject of Automotive Electrical Systems. The aim of the research was to improve the activeness and learning outcomes of Grade XI TKR 2 students at SMK Giripuro Sumpiuh through the implementation of the discovery learning model. This research was a Classroom Action Research (CAR) conducted in three cycles, each consisting of planning, implementation, observation, and reflection stages. The research subjects were 42 students, while the objects of the study included student activeness and learning outcomes. Data were analyzed using quantitative analysis techniques. The results showed an increase in student activeness, namely 52.38% in the first cycle, increasing to 64.29% in the second cycle, and reaching 74.79% in the third cycle. Learning outcomes also improved, with an average score of 47.62% in the first cycle, 64.29% in the second cycle, and 88.10% in the third cycle. Based on these findings, it can be concluded that the implementation of the discovery learning model can improve student activeness and learning outcomes in Automotive Electrical Systems for Grade XI TKR 2 students at SMK Giripuro Sumpiuh